THE EFFECT OF THE USE OF QUIZIZZ APPLICATION ON STUDENTS' LEARNING MOTIVATION ON EXCRETION SYSTEM MATERIALS IN CLASS XI IPA MAN TANJUNGPINANG - Hartati Hartati; Azza Nuzullah Putri; Bony Irawan (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2021)
This study aims to see the effect of using the Quizizz application on students' motivation on the excretory system material. This research was an experimental study with a pre-experimental design. The population in this study were all students of class XI IPA MAN Tanjungpinang. The sampling technique used a total sampling technique where the entire population was sampled so that the research sample amounted to 56 students who were grouped into control and experimental groups. The research instruments used in this study were (1) Questionnaire Instruments, to obtain data on student responses to motivation after using quizizz; (2) Learning Implementation Observation Sheet Using Quizizz, to obtain learning implementation data. Based on the results of the comparative analysis, it is known There is a significant effect on the use of the Quizizz application on students' learning motivation as indicated by the sig value. (2-tailed) 0.002 < 0.05. Quizizz can be an alternative learning media to support the learning process that can generate interest, activity, motivation and student learning outcomes.Keywords:Quizizz, interactive quiz, Motivation, Learning Outcomes, excretory system